2020
DOI: 10.1101/2020.08.26.20182709
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cardiometabolic Risk Factors for COVID-19 Susceptibility and Severity: A Mendelian Randomization Analysis

Abstract: Importance: Early epidemiological studies report associations of diverse cardiometabolic conditions especially body mass index (BMI), with COVID-19 susceptibility and severity, but causality has not been established. Identifying causal risk factors is critical to inform preventive strategies aimed at modifying disease risk. Objective: We sought to evaluate the causal associations of cardiometabolic conditions with COVID-19 susceptibility and severity. Design: Two-sample Mendelian Randomization (MR) Study. Sett… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 81 publications
5
29
1
Order By: Relevance
“…Our findings are in line with a Mendelian randomization analysis which reported that genetically increased BMI was causally associated with testing positive for COVID-19. [32] In addition, a study among UK Biobank participants reported the association between BMI and risk of testing positive was similarly shaped to the one in our study. [8] These results highlight the importance of avoiding extremely high BMI cut-offs to determine vulnerable groups to the COVID-19 disease (e.g., the NHS only considers BMIs above 40 kg/m 2 as risk groups for COVID-19).…”
Section: Possible Explanationssupporting
confidence: 80%
“…Our findings are in line with a Mendelian randomization analysis which reported that genetically increased BMI was causally associated with testing positive for COVID-19. [32] In addition, a study among UK Biobank participants reported the association between BMI and risk of testing positive was similarly shaped to the one in our study. [8] These results highlight the importance of avoiding extremely high BMI cut-offs to determine vulnerable groups to the COVID-19 disease (e.g., the NHS only considers BMIs above 40 kg/m 2 as risk groups for COVID-19).…”
Section: Possible Explanationssupporting
confidence: 80%
“…Mendelian randomization studies have analyzed potential causal associations linking 17 cardiometabolic risk factors, including BMI, with susceptibility to severe SARS-CoV-2 infection ( Leong et al., 2020 ). Although genetic predisposition to an increased BMI was associated with increased susceptibility to infection and hospitalization, this relationship was mitigated by adjustment of the genetic risk for co-existing T2D.…”
Section: Obesity and Covid-19 Outcomesmentioning
confidence: 99%
“…Mendelian Randomization (MR) has the potential to overcome two major limitations of observational studies: unmeasured confounding and uncertainties about cause and effect. Examples of MR studies elucidating risk factors for COVID-19 include two recent studies showing that BMI and smoking are risk factors for COVID-19 7,8 . We are not aware of preprinted or published MR studies of psychiatric disorders and COVID-19.…”
Section: Introductionmentioning
confidence: 99%